Behavioural synchronization from an ethological perspective: Overview of its adaptive value. (June 2016) - Duranton, Charlotte; Gaunet, Florence
Synchronized behaviours are found in various species, among all taxa of live beings. Being synchronized with other individuals is defined by doing the same thing, at the same time and at the same place as others. It is observed within intraspecific groups and dyads. We aim to provide a synthetic overview of what is behavioural synchronization and focus on the adaptive value of such a phenomenon among individuals. Then, as it is observed that some stable groups or dyads consist of individuals from different species, we finally propose to investigate the existence of interspecific behavioural synchronization.